The Impact of Service Quality at the Investment and Integrated One-Stop Service Agency on Public Satisfaction in North Kalimantan Province - Masrani, Nanang; Sriekaningsih, Ana; Patiro, Shine Pintor Siolemba (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to explore how service quality at the Investment and One-Stop Integrated Service Agency (DPMPTSP) influences public satisfaction and loyalty in North Kalimantan Province. Design/methodology/approach: The research uses a quantitative approach involving 100 respondents selected through Slovin’s formula from a population of 727,755 DPMPTSP users between January and July 2022. Data were collected using a structured questionnaire and analyzed through multiple regression with SPSS. Findings: The study finds that all five dimensions of service quality—tangibles, reliability, responsiveness, assurance, and empathy have a significant direct effect on public satisfaction and loyalty. Satisfaction also acts as a mediating variable, though the direct effect remains more dominant. Research limitations/implications: The study is limited to North Kalimantan and only considers service users of DPMPTSP within a specific time frame. Practical implications: Improving service quality in each of the five dimensions can effectively enhance both satisfaction and loyalty among the public. Originality/value: This research provides empirical evidence on the dominant role of direct service quality factors over indirect ones in shaping satisfaction and loyalty. Paper type: Research paper